2012
DOI: 10.1051/0004-6361/201117889
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic cooling and cessation of heating in the solar corona

Abstract: Context. Condensations in the more than 10 6 K hot corona of the Sun are commonly observed in the extreme ultraviolet (EUV). While their contribution to the total solar EUV radiation is still a matter of debate, these condensations certainly provide a valuable tool for studying the dynamic response of the corona to the heating processes. Aims. We investigate different distributions of energy input in time and space to investigate which process is most relevant for understanding these coronal condensations. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Recently, based upon the observed properties of the hot, and warm loops in active regions, Klimchuk et al (2010) have argued that the high concentration of heating low in the corona, and the steady or quasi-steady heating models (leading to thermal nonequilibrium) can be ruled out. However, Peter et al (2012) claim that a steady supply of energy is required even in the events of condensation in the corona, to keep the coronal pressure. They also suggested that thermal non-equilibrium can be a valuable tool in investigating the plasma dynamics and heat input in the regions where condensation forms.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, based upon the observed properties of the hot, and warm loops in active regions, Klimchuk et al (2010) have argued that the high concentration of heating low in the corona, and the steady or quasi-steady heating models (leading to thermal nonequilibrium) can be ruled out. However, Peter et al (2012) claim that a steady supply of energy is required even in the events of condensation in the corona, to keep the coronal pressure. They also suggested that thermal non-equilibrium can be a valuable tool in investigating the plasma dynamics and heat input in the regions where condensation forms.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is known that such heating is not able to keep loop atmosphere in steady equilibrium because they are thermally unstable (Antiochos and Klimchuk, 1991 ; Antiochos et al , 1999 ; Müller et al , 2004 ; Karpen and Antiochos, 2008 ; Mok et al , 2008 ). Catastrophic cooling occurs along the loops some time after the heating is switched on and might explain deviations from hydrostatic equilibrium, and some features of the light curves measured in the EUV band (Peter et al , 2012 ). However, the timescales required by this scenario seem too long compared to the measured loop lifetimes (Klimchuk et al , 2010 ).…”
Section: Loop Physics and Modelingmentioning
confidence: 99%
“…In Fig. 1 we display the synthesized emission in the AIA 171 Å channel from the computational domain showing plasma at just below 10 6 K. This image was synthesized using the AIA temperature response functions (Boerner et al, 2011;Peter et al, 2012).…”
Section: Synthesized and Real Euv Imagesmentioning
confidence: 99%